Memodifikasi Perilaku untuk Membentuk Kebiasaan Positif Baru Melalui Reinforcement - Magpirah Ulpa; Endang Setianingsih (Universitas Serambi Mekkah, 2026)
Social changes in the digital era have contributed to the emergence of various maladaptive behaviors that may hinder individual development, creating the need for effective strategies to establish sustainable positive habits. This study aims to analyze the role of behavior modification through positive reinforcement in developing new positive habits based on the perspective of behavioral psychology and previous research findings. A qualitative approach was employed using the library research method. Secondary data were collected from books, scientific journal articles, theses, and other relevant academic publications. The data were analyzed using content analysis through data reduction, data presentation, and conclusion drawing. The findings indicate that behavior modification is an effective approach to developing adaptive behaviors through the systematic application of learning principles. Positive reinforcement increases the likelihood of desirable behaviors recurring by providing pleasant consequences. Positive habit formation occurs gradually through the emergence of target behaviors, reinforcement, consistent repetition, and internalization until the behaviors become part of daily life. The synthesis of previous studies demonstrates that positive reinforcement can be effectively applied in educational, family, organizational, and community settings as a sustainable strategy for developing positive habits consistently over time.